2016
DOI: 10.1016/j.paid.2015.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Sensitivity Theory of Personality Questionnaires: Structural survey with recommendations

Abstract: This is the other version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 41 publications
4
126
0
3
Order By: Relevance
“…Currently, there are several competing RST questionnaires (for more details see Corr, 2016), which complicate the interpretation of the data. have found that the RST questionnaires differ in operationalisation of the BAS, which may bias the interpretation of the findings about the core features of RST dimensions (for example see .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are several competing RST questionnaires (for more details see Corr, 2016), which complicate the interpretation of the data. have found that the RST questionnaires differ in operationalisation of the BAS, which may bias the interpretation of the findings about the core features of RST dimensions (for example see .…”
Section: Discussionmentioning
confidence: 99%
“…The second task examines the role of the confidence (obtained by the first task), and the BAS and the BIS on the effects of positive and negative performance on motivation and self-efficacy. Finally, due to the existence of several competing RST questionnaires (Corr, 2016), two brief RST questionnaires will be used to improve the generalisability of the findings.…”
Section: Overview Of the Studymentioning
confidence: 99%
“…However, while we were able to gain some new insights into the association between trait EI and motivated behaviour, these results do not take into account significant recent developments to RST. Firstly, Carver and White's (1994) BIS/BAS scales do not contain an explicit measure of the Fight-Flight-Freeze system (FFFS) although one can be derived, albeit in a rather inadequate manner (Corr, 2016). As such, in common with the majority of other studies adopting this measure, we did not differentiate the FFFS from the BIS.…”
Section: Studymentioning
confidence: 95%
“…As such, Gray and McNaughton characterised the BIS as responsible for detecting and resolving this conflict, rather than being sensitive to punishing stimuli per se. This separation is now widely recognized, in conceptual and psychometrical terms (Corr, 2011;Gray & McNaughton, 2000;Perkins, Kemp, & Corr, 2007; for review, see Corr, 2016;Corr & Cooper, 2016). Most recently the behavioural approach system (BAS) has also been elaborated.…”
Section: Introductionmentioning
confidence: 99%
“…The RST-PQ has demonstrated good reliability and validity (Corr & Cooper, in press; see also Corr, 2016). Participants were asked how accurately each statement described them and responded on a scale from 1 (not at all) to 4 (highly).…”
Section: Reinforcement Sensitivitymentioning
confidence: 99%